1962
DOI: 10.1149/1.2425244
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Hydrocarbons in Ion Exchange Membrane Fuel Cells

Abstract: Exploratory work has been performed on the behavior of hydrocarbons and carbon monoxide in acidic ion‐exchange membrane fuel cells having platinum and palladium black electrodes. Electrical output was obtained from such cells when propane, propylene, ethylene, methane, and carbon monoxide were used as fuels. In all cases qualitative tests indicated at least partial oxidation to CO2 . All of the gases performed better on platinum than palladium. In all cases the performance improved with increasing temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The authors give no further discussion of this mechanism. Equation (51) should be further divided into two steps: (55) followed by PtOH --+ PtO + H+ + e (56) or 2PtOH --+ Pt + PtO + H 2 0 (57) PtO is probably the oxidizing species in the potential region considered (0.9-1.2 V) (the presence of adsorbed CO could increase the potential at which PtO is formed). There is no definite evidence to establish the structure of the oxygen species in different potential regions; however, the presence on Pt of several forms of surface oxide has been reported by several investigators.…”
Section: (V) Mechanistic Conclusionmentioning
confidence: 99%
“…The authors give no further discussion of this mechanism. Equation (51) should be further divided into two steps: (55) followed by PtOH --+ PtO + H+ + e (56) or 2PtOH --+ Pt + PtO + H 2 0 (57) PtO is probably the oxidizing species in the potential region considered (0.9-1.2 V) (the presence of adsorbed CO could increase the potential at which PtO is formed). There is no definite evidence to establish the structure of the oxygen species in different potential regions; however, the presence on Pt of several forms of surface oxide has been reported by several investigators.…”
Section: (V) Mechanistic Conclusionmentioning
confidence: 99%
“…For the first time, using a series of OMC-tethered molecular catalysts, we demonstrate power densities ranging from 100 to 400 μW/mg Pt (Table ), as opposed to previous technology that showed very low, unsteady open circuit voltage (OCV) at less than 105 mV and produced no measurable current from the fuel cell . Additionally, this work demonstrates substantial improvement in power density over the initial publication from the General Electric Corporation demonstrating 2.2 μW/mg Pt …”
Section: Resultsmentioning
confidence: 73%
“…Proton exchange membrane fuel cells (PEMFCs) have the advantage of much higher power densities, faster start up and shut down, good cyclability, and the potential for scalability from micro to large-scale distributed power generation; however, their lower temperature of operation makes the activation of methane extremely challenging under the operating conditions of the fuel cell. In 1962, Niedrach made the first attempt to demonstrate a DMEFC . In 2012, Ferrell et al reported methane activation using commercially available Pt ELAT and Pt–Ru ELAT gas-diffusion anode electrodes in a PEMFC .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, methane is directly used as fuel in solid oxide fuel cells, where the high operating temperatures (650–1100 °C) ease the CH 4 activation for the electrooxidative processes. For this reason, at the PEMFC working temperature (< 100 °C) methane oxidation is very challenging and the few examples of CH 4 ‐PEMFCs reported in literature have a poor activity and stability , . The authors developed an anodic catalyst based on [Pt X 2 (bpy)] (X = Cl, Ph; bpy = 2,2′‐bipyridine, 4‐4′‐dibromo‐2,2′bipyridine) or [PtX 2 (phen)] (X = Cl, Ph; Phen = 5‐bromo‐1,10‐phenanthroline) complexes chemically anchored onto an Ordered Mesoporous Carbon (OMC) support, that presents a high surface area and porosity coupled with a good electrical conductivity.…”
Section: Complete Organometallic Fuel Cells (Omfcs)mentioning
confidence: 99%